2014
DOI: 10.1111/ans.12849
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel breast reconstruction technique using the Braxon® acellular dermal matrix: a new muscle‐sparing breast reconstruction

Abstract: The preliminary results are encouraging from aesthetic and clinical viewpoints. Further studies are planned to evaluate long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 138 publications
(146 citation statements)
references
References 22 publications
3
141
1
1
Order By: Relevance
“…In the prepectoral technique, operating time is reduced as it is a less complicated technique and the surgeon can begin to perform the ex vivo procedure of suturing the Braxon ® mesh (Figure 1) around the implant after the mastectomy, while haemostasis and irrigation of the prepectoral space are being carried out. Berna et al did not report any implant loss in their small series of 15 implant-based IBR using Braxon ® and Vidya et al in a series of 100 cases has demonstrated a very low implant loss rate of 2% (18,19). However, our complication rate of wound infection and implant loss were comparable to the NMBRA results which reported on subpectoral implant based reconstruction ( Table 3) (10).…”
Section: Discussionsupporting
confidence: 58%
“…In the prepectoral technique, operating time is reduced as it is a less complicated technique and the surgeon can begin to perform the ex vivo procedure of suturing the Braxon ® mesh (Figure 1) around the implant after the mastectomy, while haemostasis and irrigation of the prepectoral space are being carried out. Berna et al did not report any implant loss in their small series of 15 implant-based IBR using Braxon ® and Vidya et al in a series of 100 cases has demonstrated a very low implant loss rate of 2% (18,19). However, our complication rate of wound infection and implant loss were comparable to the NMBRA results which reported on subpectoral implant based reconstruction ( Table 3) (10).…”
Section: Discussionsupporting
confidence: 58%
“…After a mean follow-up of 6 months, the results were extremely promising with a low rate of complications and excellent patient satisfaction regarding the cosmetic outcome. Berna et al 16 also reported a technique of prepectoral muscle-sparing breast reconstruction using a preshaped ADM (Braxon®) in 15 breasts. Using this technique, they reported no major complications, no long-term complications including capsular contracture and a satisfying aesthetic result.…”
Section: Discussionmentioning
confidence: 99%
“…A low incidence of capsular contracture was also reported in the other recent studies of prepectoral implant-based reconstruction with total ADM coverage. 15,16,18 Other studies of prepectoral reconstruction have excluded patients with large size or ptotic breasts. By using an inferior dermal flap in conjunction with an ADM, we have been able to offer prepectoral reconstruction to a wider range of patients.…”
Section: Discussionmentioning
confidence: 99%
“…This ensures fixation of the mesh implant wrap and prevents any rotation. ADM fixation is crucial to ensure primary stability and intimate contact of the matrix with the vascularized tissue, which are the basic requirements that promote remodelling of the collagen membrane [10,12]. For this reason, a quilting suture between the ADM and the subcutaneous layer is recommended before closure of the skin.…”
Section: Techniquementioning
confidence: 99%
“…The muscle-sparing technique of implant-based breast reconstruction using preshaped mesh (Braxon ® , Decomed S.r.l., Venezia, Italy) has been recently described [10]. Hence, we adopted this novel technique of prepectoral implant-based breast reconstruction in our practice, and herein present our initial experience.…”
Section: Introductionmentioning
confidence: 99%